Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Metode Pemberian Tugas Dengan Media Video pada Masa Pandemi Covid-19 Siswa Kelas II SD Negeri 4 Kuranji - Lasiati, Lasiati (Lembaga Yasin AlSys, 2021)
The objectives to be achieved in this study are: to determine the improvement of Mathematics Learning Outcomes Using the Assignment Method with Video Media During the Covid-19 Pandemic Period for Second Grade Students of SD Negeri 4 Kuranji for the 2020/2021 Academic Year. The subjects of this study were the second grade students of SD Negeri 4 Kuranji, totaling 22 people, consisting of 7 female students and 15 male students. This research uses action research in two cycles consisting of four stages, namely: design, activity and observation, reflection. The results showed that the learning outcomes of students II SD Negeri 4 Kuranji for the academic year 2020/2021, with the method of giving video media assignments could be improved with the final result of the study being the class average score in the initial conditions of 72.23 or classical completeness 54.55%, to 77.59 or 68.18% classical completeness in the first cycle, increasing to an average of 81.45 or 77.27% in the second cycle and increasing to an average test of 80.18 or 90.91% in the third cycle . From the results of student observations showed that there was an increase in student activity which in the first cycle obtained a score of 19 or 67.86% to 21 or 75.00% in the second cycle and 25 or 89.29% in the third cycle. The increase in student activities in learning Mathematics is supported by increased teacher activities in maintaining and improving the learning atmosphere using the method of giving video media assignments, this can be seen from the observations of teacher activities where in the first cycle a score of 25 or 69.44% was obtained, to 27 or 75.00% in the second cycle and increased to 32 or 88.89% in the third cycle.